2021
DOI: 10.1093/ecco-jcc/jjab070
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Ustekinumab in Ulcerative Colitis: Real-world Evidence from the ENEIDA Registry

Abstract: Background The development program (UNIFI) has shown promising results of ustekinumab in ulcerative colitis (UC) treatment that should be confirmed in clinical practice. Aims To evaluate the durability, effectiveness and safety of ustekinumab in UC in real-life. Methods Patients included in the prospectively maintained ENEIDA registry who received at least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
53
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 11 publications
10
53
0
5
Order By: Relevance
“…The finding that one-third of our patients were in CSFR following induction is consistent with recently published real world studies, though we acknowledge missing clinical data 5–8 14. Chaparro et al evaluated 95 patients from the Spanish ENEIDA registry and found CSFR rates of 30% and 32% at weeks 24 and 52, respectively 5.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The finding that one-third of our patients were in CSFR following induction is consistent with recently published real world studies, though we acknowledge missing clinical data 5–8 14. Chaparro et al evaluated 95 patients from the Spanish ENEIDA registry and found CSFR rates of 30% and 32% at weeks 24 and 52, respectively 5.…”
Section: Discussionsupporting
confidence: 91%
“…Ustekinumab treatment persistence at week 52, either actual or estimated (for cohorts with a shorter follow-up), varied between 58% to 87% across real-world studies, including our own 5–8. The variability in persistence, which is often used as a proxy for assessing sustained effectiveness, may reflect the heterogeneity of included cohorts, varying treatment regimens, and study designs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Looking at potential predictors of response, multivariate analysis showed that baseline C-reactive protein (CRP) over the upper normal value was associated with a significantly lower probability of clinical remission at week 16 [odds ratio [OR] = 0.3, 95% confidence interval [CI] = 0.1–0.7]. 22 …”
Section: Methodsmentioning
confidence: 99%
“… 16 18 Currently, few real-life data have been reported on the effectiveness of ustekinumab for UC treatment and, as it usually happens with new drugs, most of these studies included patients with prior exposure/failure to multiple biological drugs. 19 22 …”
Section: Introductionmentioning
confidence: 99%